2015
DOI: 10.5897/ajar2014.8958
|View full text |Cite
|
Sign up to set email alerts
|

Foliar tissue, grain yield and economic return by surface application of gypsum and different number of soybean plants in precision seed drill

Abstract: The gypsum has elevated calcium and sulfur in the soil, and there are reports of increased grain yield of soybean with reduced number of plants, being necessary in conjunction with economic return on investment. This study investigated the effect of application superficial of gypsum and different numbers of plants in precision seed drill in the nutritional aspect of the leaf tissue, grain yield of soybean cultivated in clayey Rhodic Hapludox and economic return on investment. Used in the experiment was a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…This might be due to the higher yields produced by gypsum source (S 1 ) of cowpea. The results are close conformity to these obtained by Rampin et al [7] reported that application @ 800 kg/ha gypsum gave significantly higher grain yield of soybean and provided US$ 14.56 profit with 44 % economic returns to pay half investment (US$ 33.32).…”
Section: Available Nutrient In Soil After Harvestsupporting
confidence: 91%
“…This might be due to the higher yields produced by gypsum source (S 1 ) of cowpea. The results are close conformity to these obtained by Rampin et al [7] reported that application @ 800 kg/ha gypsum gave significantly higher grain yield of soybean and provided US$ 14.56 profit with 44 % economic returns to pay half investment (US$ 33.32).…”
Section: Available Nutrient In Soil After Harvestsupporting
confidence: 91%
“…Without water deficiency, soybean had a low probability of responding to gypsum (37%), and the probability of crop yield increasing more than 5% in soils with Al saturation >40% was only 20% (Figure 9d). Effect on yield (%) Sávio et al, 2011Caires et al, 2016Minato et al, 2017Costa, 2015Oliveira and Paven, 1998Zandoná et al, 2015Caires et al, 2002Paulleti et al, 2014Michalovicz et al, 2014Vicensi et al, 2016Soratto and Crusciol, 2008aFreitas et al, 2017Meert, 2013Trindade, 2013Soratto and Crusciol 2008bCrusciol et al, 2016Dalla Nora et al, 2017aCaires et al, 1999Dalla Nora and Amado, 2013Sousa et al, 2010Costa and Crusciol, 2016Caires et al, 2004Fois et al, 2017Caires et al, 2011bMarques, 2008Caires et al, 2006Somavilla et al, 2016Tanaka, 2013Caires et al, 2003Arf et al, 2014Rampim et al, 2015Galleto, 2016Fontoura et al, 2018Marchesan et al, 2017Caires et al, 2011aNeis et al, 2010Rampin et al, 2011Soares, 2016Gelain et al, 2014Freitas et al, 2016Castañon et al, 2011Caires et al, 1998Leguizamón, 2017…”
Section: Probability Of a Positive Crop Response To Gypsummentioning
confidence: 99%